The quadrivalent HPV vaccine is protective against genital warts: a meta-analysis - Anita Lukács; Zsuzsanna Máté; Nelli Farkas; Alexandra Mikó; Judit Tenk; Péter Hegyi; Balázs Németh; László Márk Czumbel; Sadaeng Wuttapon; István Kiss; Zoltán Gyöngyi; Gábor Varga; et al. (BMC, 2020)
Abstract Background The quadrivalent human papillomavirus (HPV) vaccine has been assumed to give protection against genital warts (GW) as well as cervical cancer. Our main question was whether HPV vaccine has any effects on the prevention of GW reported in randomised controlled clinical trials (RCTs) and time-trend analyses. Methods This meta-analysis was performed according to the PRISMA guidelines using the PICO format. We searched in three electronic databases (PubMed, Embase, Cochrane Trials), and assessed heterogeneity using the Q-test and I-squared statistics, meta-regression was also performed. Odds ratios (OR) and their confidence intervals (CI) were calculated. The sensitivity was tested by leave-one-out method. We evaluated the presence of publication bias using the funnel plot graph and the Copas selection model. The strength of evidence was assessed using the GRADE approach. Results Eight RCTs (per-protocol populations) and eight time-trend ecological studies were included in this meta-analysis. A significant reduction (pooled OR = 0.03, 95% CI: 0.01-0.09; I-squared = 53.6%) of GW in young women was recorded in RCTs, and in time-trend analyses both in young women (pooled OR = 0.36, CI 95% = 0.26-0.51; I-squared = 98.2%), and in young men (pooled OR = 0.69, 95% CI = 0.61-0.78; I-squared = 92.7%). In subgroup analysis, a significant reduction of the number of GW events was observed especially in women under 21 years (pooled OR = 0.33, 95% CI = 0.17-0.63). Leave-one-out analysis showed that similar results could be obtained after excluding one study, meta-regression did not show significant difference. Conclusions Prophylactic, quadrivalent HPV vaccination can prevent GW in healthy women and men, therefore, it should be included in routine immunization programme.